Bulbophyllum menglaense (Orchidaceae), a new species from Yunnan, China - Li, Jian-Wu; Yin, Jian-Tao; Jin, Xiao-Hua (Phytotaxa, 2017)
Bulbophyllum menglaense, a new species of Orchidaceae from China are described and illustrated by colorful photos. Bulbophyllum menglaense is similar to B. cariniflorum and B. triste, but can be easy distinguished from them by pseudobulbs conical (vs. pseudobulbs ovoid in B. cariniflorum; subglobose in B. triste); scape longer than leaves (vs. scape shorter than leaves both in B. cariniflorum and B. triste); petals narrowly lanceolate, marings ciliate (vs. petals entire both in B. cariniflorum and B. triste); stelidia lanceolate (vs. stelidia deltoid in B. cariniflorum, narrowly lanceolate in B. triste).